436 Prognostic value of calcium scoring in changes of echogenicity in carotid plaques. (17th January 2020) - Perea Gabriel, G P; Corneli, M; Daquarti, G; Meretta, A; Rosa, D; Masoli, O
Abstract: Background: Atherosclerosis is a dynamic process, in which the characteristics of the plaques evaluated by imaging methods could represent the degree of inflamatory activity of the disease. Purpose: Assess the value of the coronary calcium score in the changes of echogenicity of carotid plaques in a population with low-intermediate cardiovascular risk. Methods: Patients with no cardiovascular history and low and intermediate Framingham risk score were evaluated. Patients attended at our institute for a preventive cardiovascular control between January 2012 and April 2013, and then a subsequent follow-up was made until January 2019. They were screened for coronary calcium scoring (CCS) and carotid plaque by ultrasound at first visit. Then the changes of carotid atherosclerotic disease were evaluated through new carotid ultrasound exam at follow up. A carotid artery plaque was defined as a localized protrusion of the vessel wall, which 1) extended into the lumen ≥ 1.5 mm, or 2) had a thickness exceeding the intima-media thickness (IMT) of the adjacent portion of the vessel wall by >50%. Plaque morphology was defined in terms of its echogenicity. Results: 121 patients that have carotid atherosclerotic disease at first carotid ultrasound exam were included. The mean age was 61 ± 9 years, 72 (59%) male patients. Cardiovascular risk factors: hypertension: 68 (56%), dyslipidemia: 46 (38%), sedentary lifestyle: 24 (20%), overweight: 17 (14%), smoking: 29 (24%) and diabetes: 15 (12%). Median distribution of CCS was 192 (percentile distribution 25-75%: 8 – 224) Agatston units. Medium follow-up: 5 ± 1 year. At first ultrasonography study, 47 patients (39%) presented hypoechoic plaques, 61 patients (50%) isoechoic plaques and hyperechoic plaques in 13 patients (11%). After the follow-up, the distribution of the plates according to their sonographic characteristics was: hypoechoic plaques in 23 patients (19%), isoechoic plaques in 55 patients (45%) and hyperechoic plaques in 42 patients (36%). The incidence of the progression of sonographic changes of the carotid plaques varies according to CCS: 0-100:29%, 101-400: 54%, >401:53% (p < 0, 001) Figure 1. The value of CCS was associated with the progression of carotid atherosclerotic plaque regardless of the use of statins and angiotensin-converting enzyme inhibitors or angiotensin 2 receptor blockers (Cox model p <0.001). Conclusions: This study shows that there is an association between coronary calcium score and progression of carotid disease. Even in populations with low and intermediate cardiovascular risk, the higher the severity of the calcium score, the greater changes in the structure of the carotid plaque manifested in our work as changes in the echogenicity; regardless of the use of statins. These findings could be useful to assess the progression of atherosclerotic disease at a median follow up.